Pengaruh Kepemimpinan, Komunikasi Dan Kompensasi Terhadap Kinerja Koperasi di Kota Tebing Tinggi - Nursaimatussaddiya, Nursaimatussaddiya; Sianipar, Christin Natalia (Management And Business Progress, 2024)
This study tries to answer the research objectives, namely to determine the Influence of Leadership, Communication and Compensation on the Performance of Cooperative Employees in Tebing Tinggi City. This study shows the Y equation which means that the variables of Leadership, Communication and Compensation are positively related to the Employee Performance variable and the three variables explain with adjusted R square. Cooperatives in Kotadimana thitung of 2.342 is greater than ttabel of 2.0395 with a significance value of 0.026. Communication affects the Performance of Cooperative Employees in Kotadimana thitung of 2.223 is greater than ttabel of 2.0395 with a significance value of 0.034. Compensation affects the Performance of Cooperative Employees in Kotadimana thitung of 2.556 is greater than ttabel of 2.0395 with a significance value of 0.016. Jointly tested with a calculated f value of 4.837 or greater than the f table value of 2.92 with a significance value of 0.007, which means that the variables of Leadership, Communication and Employee Performance have a joint effect on the Performance of Cooperative Employees in Tebing Tinggi City.